Biosynthesis and applications of nanobas for increasing bacterial leaf blight resistance in shallot - Dhadhang Wahyu Kurniawan; Nur Prihatiningsih; Nur Kholida Wulansari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Nanobas is a nanosuspension derived from Bacillus sp. isolated from the rhizosphere of shallots, formulated as a biopesticide to mitigate the predominant diseases afflicting shallots. A significant pathogen of shallots is the bacterial leaf blight caused by Xanthomonas axonopodis, which can result in yield losses of up to 80%. This research aims to: 1) develop and characterize Nanobas as a nanosuspension formula, and 2) assess the efficacy of Nanobas in enhancing the resistance of shallots to bacterial leaf blight. The experimental methodology employed a completely randomized block design in field conditions. The study comprised five treatments: P0: control, P1: Nanosuspension Bacillus sp. Bm2-chitosan 10 mL/L, P2: Bacillus sp. Bm2 liquid formula 10 mL/L, P3: Chitosan 0.01%, P4: bactericide (copper hydroxide) 2 mL/L, with each treatment replicated five times. The treatments were applied by drenching 50 mL around the plant base. The variables observed included the visual characteristics of Nanobas, incubation period, disease intensity, effectiveness, and the structural and biochemical resistance of shallots. The findings revealed that Nanobas, as a Bacillus sp. Bm2-chitosan nanosuspension, exhibited colloidal stability, characterized by its ability to scatter light without sedimentation. The application of Nanobas resulted in a 30.28% reduction in disease intensity. Structural resistance was evidenced by the increased epidermal thickness in the cell walls of shallot leaves. The highest phenolic compound content was observed in the Bacillus sp. Bm2 liquid formula treatment, indicating that while the nanosuspension formula is efficacious as a biocontrol agent, it is less effective as a bioenhancer.